Bacillus subtilis - capacity for enzymatic degradation, resistance to trace elements, antagonisms and siderophore production - Santos, Bianca De Melo Silveira Dos [UNESP]; Silva, Maura Santos Dos Reis De Andrade [UNESP]; Chávez, Davy William Hidalgo; Rigobelo, Everlon Cid [UNESP] (Southern Cross Publishing, 2021)
The use of microorganisms in agriculture as biofertilizers and biocontrol agents, in addition to their use in biotechnological practices, has been explored increasingly frequently over the years. Some bacteria, including Bacillus subtilis, have many capabilities related to promoting plant growth. The present study attempted to evaluate eight B. subtilis strains regarding their capacity for enzymatic degradation, resistance to trace elements, antagonism against phytopathogenic fungi and siderophore production. The tests were performed in plate dishes and test tubes with six repetitions for each bacterial isolate. The results showed that all isolates were able to perform enzymatic degradation to phosphatase, amylase and cellulase. Regarding resistance to trace elements, for Cd, 0.5 mmol L-1 was sufficient to prevent the development of strains 248, 263 and 320; for Cu, isolate 263 obtained greater resistance; for Zn, isolate 320 was inhibited at 2.0 mmol L-1, for Cr(III), isolates 290 and 291 showed greater resistance to the metal, whereas for Cr(VI), isolates showed the same resistance pattern; and for Ni, isolates showed the same resistance behavior. In vitro antagonism occurred for all isolates; however, the antagonism occurred at different intensities, except for isolate 291. The production of siderophores was identified for only six isolates: 287, 320, 309, 274, 263 and 248. These results establish a foundation for further investigations to clarify the conditions and/or characteristics required by isolates for a more effective performance, observing metabolic routes and genetic mechanisms.
Keywords: Antagonism; Bacillus subtilis; Bioremediation; Biotechnology; Siderophores